THE EFFECT OF ADDING CARROT EXTRACT AS A NATURAL DYE ON AMPLANG SHRIMP CRACKERS - bayu kesuma dewa; Dewita Dewita; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT This study aims to determine the effect of adding carrot extract to prawn crackers. This research consisted of 2 stages, namely making carrot extract and making prawn crackers with the addition of carrot extract coloring at different levels. The method used was to make prawn crackers with the addition of carrot extract coloring with 4 treatment levels, namely: 0% (control), 10%, 15%, and 20%, and repeated 3 times. The test results showed that carrot extract had a significant effect on taste, aroma, texture, appearance and color. The results showed that the addition of 10% (W1) carrot extract was the best treatment with average values including appearance 6.86 (bright color, clean), aroma 6.77 (product specific strength), texture 6.98 (crispy, solid) and taste 6.80 (quite strong specific for shrimp). Proximate values include 3.97% water content, 2.68% ash content, 4.38% protein content, and 21.07% fat content. Keywords: Amplang, Addition, Carrot. 1). Student of Faculty of Fisheries and Marine Sciences, University of Riau 2). Lecturers of Faculty of Fisheries and Marine Sciences, University of Riau